Monitoring Heartbeats, temperature and Infusion in Patients Based Microcontroller (ARDUINO MEGA2560) - Muhammad Ridhan Firdaus (Telekontran : Jurnal Ilmiah Telekomunikasi, Kendali dan Elektronika Terapan, 2017)
Monitoring heartbeat, temperature and infusion in patients is a method that can help nurses and physicians in monitoring the progress of the patient's health to determine which patients priority should be given special treatment. As well as biomedical monitoring is equipped with a user interface that is capable o displaying 3 parameters heart rate, temperature and infusion in patients with the following enhancements as an indicator buzzer sounds when there is abnormal in patients. These three parameters are used as an indication of the development of the patient's health significantly. The body temperature is necessary because in addition it could be an indicator kesehataan someone, also has little to do with the performance of the heart, ie the temperature of the body away from the normal body condition then it affects the fast or slow heart pumps blood throughout the body. Monitoring tools necessary for the function of the drip infusion is crucial as auxiliary fluid metabolism, due to delays in the replacement of the infusion, and in the event of an interruption in the infusion liquid droplets can be fatal risk that can even cause death for patients with certain conditions. In addition, the device drip montioring this may be the right tools for hospitals with health resources (paramedics) are limited, so as to reduce the burden of paramedics.